STRATEGI DIPLOMASI HALAL: ANALISIS PASAR GLOBAL DAN INOVASI PRODUK HALAL - Amanullah, Athif; Dzikri, Yushalluna (Taksasila Edukasi Insani, 2024)
Halal diplomacy is a strategic tool to boost the competitiveness and export of Indonesian halal products. Global trends show that consumer interest in halal products extends beyond religion, focusing on quality, safety, and sustainability. Thus, innovation and effective diplomacy are vital for expanding market reach. This study examines halal diplomacy strategies and the role of product innovation in strengthening Indonesia’s exports. Using a qualitative approach and literature review, data were gathered from government policies and relevant studies. Descriptive analysis identified patterns and strategies to enhance exports. The research aims to analyze Indonesia's halal diplomacy strategies, explore the role of innovation, and identify challenges and opportunities in global markets. Findings highlight the use of multilateral and bilateral diplomacy to expand market access. Recognized halal certification and collaboration with international certification bodies are critical success factors. Additionally, innovation, including technology and product diversification, boosts competitiveness. Despite these efforts, challenges such as harmonizing halal standards and enhancing global promotion persist.Keywords: Halal Diplomacy, Halal Product Innovation, Exports, Global Market, Islamic Economic Strategy.